Innovation model for MSMEs recovery business strategy: Lessons from tourism area during the COVID-19 pandemic - Fitriaty Fitriaty; Dessy Elliyana; Fitri Widiastuti (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This study aims to analyze the performance of MSMEs in tourist areas in Jambi Province by integrating innovation models and recovery strategies during the COVID-19 pandemic. The research was conducted in several main tourist areas in Jambi Province. The population in this study were all MSME entrepreneurs in the selected tourist area, with a sample of 151 entrepreneurs. The data is sourced from interviews (questionnaire-based) with MSME entrepreneurs and in-depth interviews with MSME entrepreneurs, the Jambi Provincial Tourism Office, and the Jambi Province Industry and Trade Office. The data were analyzed with the SEM-PLS analysis tool. The analysis found that competitive strategy and innovation positively affected the productivity of MSMEs. Likewise, productivity has a positive effect on the performance of MSMEs. Furthermore, there are three main strategies to recover the MSME business: digitizing business, controlling and assessing supply chains, and utilizing business assistance from the government.